THE POLICY OF QUOTAS AS A MECHANISM FOR FACING POVERTY AND DEMOCRATIZATION OF HIGHER EDUCATION: AN ANALYSIS OF THE EFFECTS OF EDUCATIONAL INEQUALITY IN THE EXERCISE OF CITIZENSHIP AND BRAZILIAN SOCIAL JUSTICE - Gomes da Silva Muylaert Monteiro de Castro, Bianca; Martins Rangel, Etuany; José Gomes da Silva Castro, Maria; Felipe Câmara Borges, Luís; Campos de Souza Amaral, Shirlena (LINKSCIENCEPLACE, 2026)
The present work, through a bibliographical review, seeks to analyze how the implementation of the quota policy happened, following the justification of affirmative actions and their effects on society. The laws of quotas in higher education institutes are recent legal provisions, implemented since 2001, which aim to act in a compensatory and reparatory way, in order to reduce the inequalities established historically. Quotas are focused and temporary measures that seek to insert minorities into the educational context. When it comes to reserving vacancies for black, pardo, indigenous, low-income or disabled students, work focuses on access to education, since ensuring access to people belonging to all social classes means democratizing The university, is to be in accordance with the constitutional principles of equality and human dignity, seeking to offer autonomy through education, providing training for the labor market. The study also finds that people in poverty have their chances stolen because many even consider joining the university. However, the work intends to demonstrate the need to include these minorities in the educational context so that there can be flexibility and mobility of social classes, considering that the non-occupation of educational spaces by the minorities in question is attributed to the individual question, constructing In the social imaginary the perspective of lack merit, of accommodation, disregarding the real conditions in which these people live. In this way, we will analyze whether the existing norms are applied in the concrete case and attend to the students in a satisfactory way, from the perspective of social justice brought by the policy, since in many cases, there is a gap between the law and its Taking into account educational reflexes in other spheres of life of individuals and viewing it as a mechanism for confronting poverty and creating a new way of viewing the world through which citizenship can be exercised and social inequalities reduced.